Commentary: Intense Upper Mantle Hydration of the Pacific Plate Beneath the Southern Mariana Trench - Eduardo Contreras‐Reyes (Geophysical Research Letters)
Abstract To date, estimates of mantle serpentinization in trench‐outer rise regions have largely relied on Vp models from controlled‐source seismic experiments. A recent study by He et al. (2025; https://doi.org/10.1029/2024GL113792) presented both Vp and Vs models along a seismic profile crossing the southern Mariana Trench near the Challenger Deep. This region is considered an end‐member type subduction zone, where the old Pacific Plate subducts steeply with pronounced slab curvature. The study revealed low Vp and Vs values and high Vp/Vs ratios of ∼1.95 in the uppermost mantle, indicating a high degree of hydration. These ratios are higher than those found in young oceanic plates (1.81–1.83) and much greater than those for dry peridotite (1.73–1.75). The results emphasize the importance of recording both P‐ and S‐waves in trench settings to assess serpentinization, as outer‐rise faults in both old and young oceanic plate can channel fluids into subduction zones potentially in different ways.